2016
DOI: 10.1177/1354068815583200
|View full text |Cite
|
Sign up to set email alerts
|

Election outcomes, legislative representation, and satisfaction with democracy

Abstract: This paper disentangles the relationship between election outcomes and satisfaction with democracy. As the first comparative study to employ a measure of satisfaction immediately before and after elections, we can be unusually confident that any changes we observe are attributable to election outcomes. Following previous work, we affirm that voting for parties that win more votes, more legislative seats, and more cabinet seats boosts satisfaction with democracy. In addition, we demonstrate for the first time t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(88 citation statements)
references
References 41 publications
2
85
0
1
Order By: Relevance
“…In this study, we found that supranational elections decrease satisfaction both among voters and abstainers. Similar negative effects can be expected in other contexts in which elections produce outcomes that are seen as distorted, illegitimate or ineffective, and it may affect especially those who voted for parties that fail to gain any representation (Blais, Morin-Chassé, and Singh 2015). For instance, satisfaction may decrease among those voters in the United States whose preferred presidential candidate loses the White House despite winning the popular vote, as did the Democratic candidate in 2000 and 2016 (Craig et al 2006).…”
Section: Predicted Pre-post Change In Satisfaction With Democracy By mentioning
confidence: 86%
See 1 more Smart Citation
“…In this study, we found that supranational elections decrease satisfaction both among voters and abstainers. Similar negative effects can be expected in other contexts in which elections produce outcomes that are seen as distorted, illegitimate or ineffective, and it may affect especially those who voted for parties that fail to gain any representation (Blais, Morin-Chassé, and Singh 2015). For instance, satisfaction may decrease among those voters in the United States whose preferred presidential candidate loses the White House despite winning the popular vote, as did the Democratic candidate in 2000 and 2016 (Craig et al 2006).…”
Section: Predicted Pre-post Change In Satisfaction With Democracy By mentioning
confidence: 86%
“…Blais and Gélineau (2007) found a positive effect on voters in general and winners, particularly in the Canadian election of 1997. Finally, Blais, Morin-Chassé, and Singh (2015) found that satisfaction increased among those who voted for parties that gained greater shares of votes, seats, and cabinet portfolios. All these findings reveal that the use of post-electoral measures of satisfaction can be a risky strategy since causality may go in the opposite direction.…”
Section: Hypothesis 5: Satisfaction With Democracy Increases the Mostmentioning
confidence: 99%
“…On a most basic level, voters whose preferred party wins in elections show higher levels of satisfaction (Anderson & Guillory ; Blais et al. ). Beyond that, ideological or issue congruence with the government (Curini et al.…”
Section: Previous Research and Theoretical Argumentmentioning
confidence: 99%
“…For example, Singh () notes that the effect of winning on democratic satisfaction is particularly pronounced for voters who selected winning parties to which they have strong partisan attachments. Moreover, Blais, Morin‐Chassé, and Singh () find that the relationship between winning and satisfaction is moderated by the characteristics and performance of the party that one supports (see also Curini, Jou, & Memoli, ; Singh & Thornton, ).…”
Section: Interpretations Of Election Outcomesmentioning
confidence: 99%